Performance Analysis of Signalised Staggered Intersection At Jalan Pasir Pelangi, Johor Bahru, Johor - Budiman, Nurfadilah; Ahmad Termida, Nursitihazlin (Recent Trends in Civil Engineering and Built Environment, 2024)
As traffic volume increases, congestion at intersections increases as well. Congestion on roadways and signalised intersections has posed significant problems throughout the world. This study is done at the signalised staggered intersection at Jalan Pasir Pelangi in Johor Bahru namely the signalised intersection of Jalan Pasir Pelangi/Jalan Bakar Batu (Site 1) and Jalan Pasir Pelangi/Jalan Persisir Pantai (Site 2). The aim of this study is to improve signalised staggered intersection since the increasing traffic demand resulting in worsen of traffic congestion. The current performance is evaluated in terms of Level of Service (LOS), Degree of Saturation (DOS) and queue length by collecting data for one-weekday and one-weekend in the morning, noon and evening peak hour sessions in which one-hour data was collected in each session. Then the data were used as input in Signalised Intersection Design and Research Aid (SIDRA) Software Version 8.0. The analysis showed that signalised staggered intersection at Jalan Pasir Pelangi were the worst on weekday during noon peak hour and weekend during evening peak hour with overall intersection of Site 1 during noon peak hour on weekday was LOS C meanwhile on the overall intersection of Site 2 was LOS F. For the evening peak hour on weekend, the overall intersection of Site 1 was LOS D whereas on the overall intersection of Site 2 was LOS F.